Abelhas visitantes florais e polinizadoras do morangueiro (Fragaria x ananassa Duch.) cultivado em ambiente tropical - Oliveira, Pedro de Assis de (2024)
The aim of this study was to understand the floral biology and pollination requirements of strawberry (Fragaria x ananassa Duch.) in a tropical environment, as well as to identify potential pollinating bees under these conditions, with emphasis on the behavior and efficiency of stingless bees (Nannotrigona testaceicornis (Nat), Plebeia flavocincta (Pf), Scaptotrigona aff. depilis (Sad) and Trigona recursa (Tr)) and the stinging bee Apis mellifera (Am), in addition to the effect of the introduction of Sad colonies on the pollination of the San Andreas cultivar, in the municipality of Tianguá-CE. To monitor the floral biology, flowering plants were counted, floral age was determined (anthesis to senescence), floral morphometry was performed in primary and secondary flowers, and stigmatic receptivity test with hydrogen peroxide. For pollination requirements, the following treatments were performed: open pollination (Pl), manual cross-pollination (Pmc) and restricted pollination (Pr)/spontaneous self-pollination (Ape). In order to evaluate the effect of Pmc per flowering day and Pl, the days were used as treatment. To compare the pollination efficiency among Sad, Am, Tr, Pf and Nat bees, one visit was used. Different numbers of visits by Sad were evaluated and compared with the Ape and Pl treatments. The results showed that the flowers remained open for four days. There were significant differences between the primary and secondary flowers (p<0.05) for sepal length and width and largest stigma diameter. The flowers are receptive from the first day of flowering. PL and Pmc obtained 100% of set fruits and Pr only 50%. There were significant differences (p<0.05) between the Pmc and Pl treatment variables by floral age. A total of 19 bee species visited the strawberry flowers. The most abundant were Sad, Am, Tr, Pf and Nat, with visits between 6:00 a.m. and 5:00 p.m. All bees touched the reproductive structures of the flowers. Strawberry weight ranged from 6.66 g (Ape) to 12.43 g (Pmc) and 13.58 g (Pl). The Tr and Ape treatments did not produce fruits in size 3 (diameter >30 mm), while size 2 (between 20 and 30 mm) was the most frequent in all treatments. The percentage of fruits within commercialization standards ranged from 11% (Ape) to 92% (Nat). When evaluating the pollination efficiency by floral age, the Sad, Tr and Pl treatments did not show significant differences (p>0.05) for weight. The introduction of Sad increased fruit quality from 33% to 58%. Flowers that were exposed to free visitation by Sad bees produced fruits with better conformation (100%), but the heaviest fruits were produced in flowers exposed to all visitors (complementarity) and when they received more than three Sad visits (p<0.01). It is concluded that the studies of floral biology and pollination requirements in primary flowers indicate the need for agents for cross-pollination of the studied cultivar. The evaluated species Sad, Am, Tr, Pf and Nat present foraging behaviors compatible with providing the pollination services required for strawberry plants under the studied tropical conditions, reflecting positively on the quantitative and qualitative variables desired for the crop.